Nationwide access to an internet‐based contingency management intervention to promote smoking cessation: a randomized controlled trial. (25th January 2017) - Dallery, Jesse; Raiff, Bethany R.; Kim, Sunny Jung; Marsch, Lisa A.; Stitzer, Maxine; Grabinski, Michael J.
Abstract : Background and aims: Contingency management (CM) is one of the most effective behavioral interventions to promote drug abstinence, but availability of this treatment is limited. We evaluated the efficacy and acceptability of internet‐based CM relative to an internet‐based monitoring and goal‐setting control group in a nationwide sample of cigarette smokers. Design: Randomized controlled trial with 3‐ and 6‐month follow‐ups. Setting: United States. Participants: Smokers ( n  = 94) from 26 states were enrolled (mean age 36, 56% female). Intervention and comparator: Participants were randomized to earn financial incentives (up to $480 over 7 weeks) based on video‐verified abstinence using breath carbon monoxide (CO) output ( n  = 48; abstinent contingent group, AC), or based on submitting CO samples ( n  = 46, submission contingent, SC). Both groups also received the same CO‐based goals. A $50 deposit was required in both groups that could be recouped from initial earnings. Measures: The primary outcome was point prevalence at week 4. Secondary outcomes were point prevalence at the 3‐ and 6‐month follow‐ups, percentages of negative CO samples, adherence to the CO sampling protocol, and treatment acceptability ratings on a 0–100‐mm visual analog scale. Findings: Abstinence rates differed at 4 weeks between the AC (39.6%) and SC (13.0%) groups [odds ratio (OR) = 4.4, 95% confidence interval (CI) = 1.6–12.3], but not at the 3‐ (29.2% AC and 19.6% SC, OR = 1.7, 95% CI = 0.6–4.4) or 6‐ (22.9% AC and 13.0% SC, OR = 2.0, 95% CI = 0.7–5.9) month follow‐ups. During the two main treatment phases, there were significant differences in negative COs (53.9% AC and 24.8% SC, OR = 3.5, 95% CI = 3.1–4.0; 43.4% AC and 24.6% SC, OR = 2.3, 95% CI = 1.6–3.4). Adherence to the CO submission protocol was equivalent (78% AC and 85% SC, difference = 7.0%, 95% CI = −10.3 to 23.8 %, F < 1, P = 0.39). The lowest acceptability ratings were for the items assessing the deposit, whereas the highest ratings concerned the ease of the intervention, the graph of CO results, and earning money. Conclusions: A contingency management/financial incentive program delivered via the internet improved short‐term abstinence rates compared with an internet program without the incentives.